Vestibular dysfunction after cochlear and auditory brainstem implantation: Madras ENT Research Foundation experience - Natarajan, Kiran; Murali, Sathiya; Kumar, Santhosh M.; Anandappa, Manjunatha H.; Panicker, Adarsh; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Cochlear implantation is an established procedure for patients with bilateral severe to profound sensorineural hearing loss. CI may, in some implantees, have a detrimental impact on vestibular function. Auditory brainstem implantation is a safe and effective procedure in children with bilateral cochlear and cochlear nerve aplasia. The aim of the study was to assess the impact of cochlear implantation and auditory brainstem implantation on the vestibular function. Methods: Three hundred and twenty patients who underwent CI surgery over a four years period from November 2016 to November 2020 were studied for symptoms of vestibular disturbance. Twenty three patients complained of giddiness and underwent vestibular function testing including videooculography, caloric test and vestibular evoked myogenic potentials. 48 patients with cochlear and cochlear nerve aplasia underwent ABI surgery from September 2009 to March 2019. The correlation between the size of the flocculus and the presence of vestibular symptoms was studied. Results: After CI, vestibular disturbances were seen in 23 patients (7.2%) and were transient. In auditory brainstem implantees, vestibular disturbances were seen in eight patients (16.7%) and were found to correlate with the size of the cerebellar flocculus. Conclusions: Vestibular disturbances are rare after cochlear and auditory brainstem implant surgery. During CI, the preservation of vestibular function should be attempted using minimally invasive techniques. ABI surgery requires meticulous dissection, especially of a large cerebellar flocculus to minimize the possibility of vestibular disturbances.